Corporate Reputation Construction through Media Public Relations Strategies on Instagram - Mohammad Insan Romadhan; Sumiati (Kirana Publisher (KNPub), 2026)
The development of social media has transformed Public Relations practices in building corporate reputation through more interactive and participatory digital communication. Instagram, as a visual-based platform, has become one of the strategic media used by organizations to construct reputation through digital content management. This study aims to analyze the construction of corporate reputation through Media Public Relations strategies on Instagram implemented by Royal Fragrance. This research employs a qualitative approach with a case study method. Data collection techniques include non-participant observation of Royal Fragrance’s Instagram account, documentation of digital content, and literature review to strengthen the theoretical analysis. The data analysis technique uses an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the construction of Royal Fragrance’s corporate reputation through Instagram is carried out through five main strategies: visual content management, audience interaction, influencer collaboration, brand storytelling, and digital communication consistency. Consistent visual content management helps build a premium and professional brand image. Audience interaction through digital communication features strengthens the relationship between the organization and its public. The use of influencers enhances brand visibility and social legitimacy. Furthermore, brand storytelling and consistent digital communication reinforce organizational identity and increase public trust. This study concludes that Instagram-based Media Public Relations plays a significant role in building corporate reputation in the era of digital communication. The findings contribute theoretically to the development of digital Media Public Relations and corporate reputation studies, while also providing practical implications for organizations in managing reputation through social media.